Policymaking in a 'Christian nation': women's and LGBT+ rights in The Bahamas' 2016 referendum. Issue 1 (2nd January 2017) - Wallace, Alicia
ABSTRACT: In 2014, a gender equality referendum was announced in The Bahamas. Four bills were presented in an attempt to neutralise transference of citizenship under the constitution and add sex to the prohibited grounds of discrimination. Dates were announced and postponed several times while the appointed Constitutional Commission conducted its educational campaign. In 2016, a new date was finally announced, and the campaign against gender equality grew in strength and number of supporters, led by religious leaders. Where misogyny failed, homophobia and xenophobia scared and angered the majority, and it became clear that the bills would fail in referendum. The No Campaign run by religious leaders, in churches and public spaces, was one that depended on fear, conservative leanings, and fundamentalist interpretations of The Bible. This article focuses on the experience of the gender equality campaign, focusing on the voice and role of the LGBT+ community, opposing legal authorities, and combating the harmful ideas put forth by fundamentalist and conservative elements in the Christian church over a two-year period.